2010
DOI: 10.1097/qai.0b013e3181e19a6b
|View full text |Cite
|
Sign up to set email alerts
|

Intentional Risk Reduction Practices of Men in Switzerland Who Have Anal Intercourse With Casual Male Partners

Abstract: Although condom use is the most frequent protection strategy in anal intercourse with casual partners, risk reduction practices are highly prevalent. However, there are no clear differences regarding predictors between risk reduction practices and inconsistent or no condom use. This suggests that risk reduction is an opportunistic response rather than a strategy per se.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…This is significantly higher than what has been found in other studies [58, 42, 48]. Selection bias likely explains this difference since recruitment took place at Spot, a community-based HIV testing site.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…This is significantly higher than what has been found in other studies [58, 42, 48]. Selection bias likely explains this difference since recruitment took place at Spot, a community-based HIV testing site.…”
Section: Discussionmentioning
confidence: 62%
“…In studies among MSM, 25–75 % of respondents reported using seroadaptive strategies [58, 42, 48], with 25–50 % saying they used serosorting [7, 8, 37, 45, 49, 50] and 6–30 % reporting the use of strategic positioning [5, 6, 8, 32, 48]. Consideration of viral load is less documented and only a small proportion of MSM appear to use it for risk reduction [32].…”
Section: Introductionmentioning
confidence: 99%
“…Our data also suggest that the rollout of PrEP in San Francisco and the developed world may affect decisions on seroadaptive and conventional risk reduction strategies adopted by MSM, how they are communicated and how they are perceived in terms of transmission risk 27. While there is ample evidence of seroadaptive practices in developed countries,31 35 little is known about the adoption of these practices by MSM in the rest of the world, particularly considering lower levels of HIV testing and status awareness 36–38. As the established HIV epidemics in MSM in the developed world continue to evolve, and communities of MSM in the rest of the world become larger and more visible, a thorough understanding of seroadaptive behaviours—their prevalence, intentionality, effectiveness and safety—can help guide HIV and STI prevention efforts.…”
Section: Discussionmentioning
confidence: 99%
“…In that study, no significant differences were found in the key characteristics of men who reported consistent condom use; unprotected anal intercourse with casual partners (UAIC) employing additional serosorting, strategic positioning or withdrawal strategies; or UAIC with no such strategies. The Swiss findings suggest that the use of risk-reduction strategies during UAIC may be an opportunistic response rather than a planned strategy 20. Two San Francisco studies in 2004 and 2008 found that the use of UAI risk-reduction strategies differed by HIV status 21 22.…”
mentioning
confidence: 92%
“…Also, in the literature, UAI risk-reduction strategies have been given various definitions, mostly inferred from descriptive behavioural patterns. The Swiss study is the only one that evaluated both intentions to use and adoption of UAI risk-reduction strategies 20. In that study, no significant differences were found in the key characteristics of men who reported consistent condom use; unprotected anal intercourse with casual partners (UAIC) employing additional serosorting, strategic positioning or withdrawal strategies; or UAIC with no such strategies.…”
mentioning
confidence: 99%